2018
DOI: 10.3389/fimmu.2018.01126
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Fragment of Human Surfactant Protein D induces Apoptosis in Pancreatic Cancer Cell Lines via Fas-Mediated Pathway

Abstract: Human surfactant protein D (SP-D) is a potent innate immune molecule, which is emerging as a key molecule in the recognition and clearance of altered and non-self targets. Previous studies have shown that a recombinant fragment of human SP-D (rfhSP-D) induced apoptosis via p53-mediated apoptosis pathway in an eosinophilic leukemic cell line, AML14.3D10. Here, we report the ability of rfhSP-D to induce apoptosis via TNF-α/Fas-mediated pathway regardless of the p53 status in human pancreatic adenocarcinoma using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
0
34
0
Order By: Relevance
“…Translocation of NF-κB from the cytoplasm into the nucleus of pancreatic cancer cell lines was observed following treatment with SP-D. SP-D treatment caused upregulation of pro-apoptotic marker Fas, which then triggered cleavage of caspase 8 and 3. This study raises the possibility of using recombinant SP-D as a therapeutic molecule against pancreatic cancer irrespective of their p53 phenotype ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Translocation of NF-κB from the cytoplasm into the nucleus of pancreatic cancer cell lines was observed following treatment with SP-D. SP-D treatment caused upregulation of pro-apoptotic marker Fas, which then triggered cleavage of caspase 8 and 3. This study raises the possibility of using recombinant SP-D as a therapeutic molecule against pancreatic cancer irrespective of their p53 phenotype ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of SP-D in the regulation of the inflammation and homeostasis and in the protection against infection and allergens in the lung and at a range of extra-pulmonary mucosal sites is well documented ( 26 , 27 ). However, there are recent evidences to implicate SP-D as an immune surveillance molecule against cancer ( 19 , 20 ). In this study, we examined the potential prognostic value of this protein in lung, gastric, breast, and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Umeda et al [15] reported that high serum SFTPD levels were associated with a lower number of distant metastases and better prognosis. Besides, recent studies also suggested that SFTPD could suppress the progression of pancreatic cancer by inducing epithelial-mesenchymal-transition (EMT) and apoptosis of pancreatic cancer cells [16,17]. Furthermore, SFTPA and SFTPB have been proposed to function as tumour suppressor genes as well, and their downregulation was closely related to poor prognosis of patients with lung cancer [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, it has been proposed that SFTPD expression was associated with tumour progression and survival of patients with lung cancer [13][14][15]. Furthermore, recent evidence also showed that SFTPD could suppress the progression of pancreatic cancer by inducing epithelial-mesenchymal-transition (EMT) and apoptosis of pancreatic cancer cells [16,17]. In addition, it has also been suggested that SFTPA and SFTPB might function as tumour suppressor genes and their dysregulation were closely related to poor prognosis of lung cancer patients [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%